Seismic behavior of spun precast concrete pile in liquefiable reclaimed soil of Suburban Dhaka - Kh. Afia Farzana; Mehedi Ahmed Ansary; Khondaker Sakil Ahmed (Discover Civil Engineering)
Abstract Pile foundations can encounter failure during seismic excitations due to large lateral deflection that may arise from the soil liquefaction and generation of the P-Delta (P-D) induced excessive moment, particularly in reclaimed soil. A spun prestressed concrete (SPC) pile is a reliable alternative as it is usually constructed with high-strength concrete with more precision in the process of casting, curing, and monitoring. Considering the exact site soil properties of a reclaimed site, Jolshiri area of Dhaka, Finite Element Models (FEM) have been developed for predicting the actual response of SPC pile using PLAXIS 3D. The developed FE model has been validated with the actual vertical bearing capacity of the pile as obtained from the onsite pile load test. A parameter dependency study has been conducted to understand the influence of mesh sizes, pile length, and diameter. Moreover, the performance of the pile for both short and long-duration ground motions in liquefiable soil has been investigated considering soil-pile interactions. The UBC3D-PLM has been used to capture the seismic behavior and liquefaction phenomenon, respectively. Pile performance has been assessed with and without soil liquefaction for Kobe and Loma Prieta ground motions. Lateral displacement of the spun precast concrete pile (SPC) pile is observed to be increased by 11–26 times due to the earthquake ground motions than that obtained from the static loading condition. In addition, the liquefaction phenomenon increases the lateral displacement of the pile by 30–60% compared to that in non-liquefied soil conditions. The earthquake with a longer period has a significant influence on the pore pressure increment and also a reasonably high seismic force demand is perceived at the contact area of the liquefiable and non-liquefiable soil layer.